Hands Across the Río de la Plata: Argentine and Uruguayan Antifascist Women, 1941-1947 - McGee Deutsch, Sandra (Contemporánea, 2022)
The Junta de la Victoria, an Argentine women’s antifascist group, arose in September 1941. Inspired by goals resembling those of the Junta, and similarly linked to the Communist party, Acción Femenina por la Victoria was founded in Uruguay in May 1942. Both became Popular Front associations, with thousands of diverse members who produced clothing and supplies for the Allies, defended democratic ideals, and promoted women’s citizenship. At rst the Junta was Accion Femenina’s mentor, yet the relationship shifted into a dee- per, more reciprocal alliance that enabled the organizations to ful ll their mission. e in- tertwined histories of the Junta de la Victoria and Acción Femenina por la Victoria o er an extraordinary example of antifascist women’s transnational collaboration.